2020
DOI: 10.1021/acsami.0c08531
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide–Doxorubicin Conjugate as a Double Intercalating Agent and Delivery by Apoferritin for Glioblastoma Chemotherapy

Abstract: We designed a conjugated compound by coupling temozolomide (TMZ) with doxorubicin (DOX) via an acylhydrazone linkage as a potential prodrug used for glioblastoma multiforme (GBM) treatment. Viscosity and spectroscopic studies revealed that the drug conjugate could act as a nonclassical double intercalating agent. Although free TMZ is an inefficient DNA binder in comparison to DOX, the TMZ moiety interacted with DNA as an induced intercalator, arising from the synergistic effect of DOX moiety that mediated conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 68 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…It was generally believed that doxorubicin has a limited capacity to penetrate the blood-brain barrier and thus the brain is protected from its damage. However, several studies have shown that doxorubicin has potential antitumor effects on brain cancer ( 14 ). Clinical as well as animal studies have shown that doxorubicin was detected in the brain after peripheral administration of the drug ( 15 , 16 ).…”
Section: Direct Neurotoxicitymentioning
confidence: 99%
“…It was generally believed that doxorubicin has a limited capacity to penetrate the blood-brain barrier and thus the brain is protected from its damage. However, several studies have shown that doxorubicin has potential antitumor effects on brain cancer ( 14 ). Clinical as well as animal studies have shown that doxorubicin was detected in the brain after peripheral administration of the drug ( 15 , 16 ).…”
Section: Direct Neurotoxicitymentioning
confidence: 99%
“…DOX is an anthracycline antibiotic chemotherapy agent and is one of the most extensively used antitumor drugs ( 94 ). Its main mechanism of action is by quickly entering the nuclei of tumor cells and inhibiting the proliferation of tumor cells by binding to DNA and blocking DNA replication ( 95 , 96 ). DOX has been found to inhibit the proliferation of glioma cells.…”
Section: Other Chemotherapy Agentsmentioning
confidence: 99%
“…[81] It is also found that the drug-drug conjugate may change the mechanism of action, exemplified by temozolomide (TMZ)-Dox prodrug double intercalating with DNA although TMZ itself is a weak DNA binder and functioned as an induced intercalator. [82] Figure 5. A) Synthesis of PTX 2 and Self-assembly of PTX 2 in aqueous solution.…”
Section: Chemical Reaction Obtained Drug-drug Conjugate Prodnmsmentioning
confidence: 99%